Efeitos da consistência do sistema de gestão de desempenho de recursos humanos no engajamento no trabalho: enfoque no papel interveniente da justiça organizacional e do estilo de liderança - Guimarães, Duanne Emanuel Leal (2022)
The study aims to analyze the effects of the consistency of the human resources performance management system on work engagement, mediated by organizational justice and moderated by leadership style, in a Federal Public Authority. Inserted in a positivist perspective, quantitative, descriptive research, specifically by a survey single entity, develops a behavioral approach, under the levels of organizational and individual analysis. The work sample included the participation of 132 public servants, among managers and non-managers, who participated in personnel performance evaluation processes. The theoretical relationships between the constructs were tested using structural equation modeling. The analyzed constructs were the consistency of the human resources performance management system (CSGDRH), engagement at work, organizational fairness and leadership styles. The research findings demonstrate a significant and positive relationship between CSGDRH and engagement at work, between CSGDRH and organizational justice, as well as between the latter and engagement at work, which allows us to infer that CSGDRH and organizational justice are predictors of engagement at work. A mediating effect of organizational justice was observed in the relationship between CSGDRH and engagement at work, however, the moderation of leadership style in the relationship between perception of organizational justice and engagement at work, as well as the intervening effects of the global model, was not confirmed. of analysis. These findings reveal that CSGDRH enhances engagement at work, which is directly and indirectly influenced by organizational justice. The results partially converge with the literature regarding leadership styles, since there are inconsistencies when analyzing different contexts and environments. It is concluded that the CSGDRH positively influences engagement at work and, together, organizational justice has a mediating effect, however, the moderation of leadership styles is not confirmed. The results offer a perception of the importance of CSGDRH in the public sector and contribute by reaffirming that behavioral factors of employees are a significant part in the search for better organizational results.